2017
DOI: 10.55095/achot2017/069
|View full text |Cite
|
Sign up to set email alerts
|

Cement Augmentation of the Cervical Spine - a Technique Enhancing Stability of Anterior Cervical Plating

Abstract: One option is to perform anterior and posterior surgery to increase the stability of the surgery performed (12,16,27). However, this will involve putting patients through a second operation, which may be poorly tolerated (prone position, lengthy spine exposure with risks of infection, blood loss and an often prolonged operating time), in a frequently frail, or generally unwell, population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The technique, including ventral cervical plate and cement augmentation, is designed to restore structural integrity. This method aligns with findings from prior studies that have demonstrated positive outcomes, with similar procedures aimed at stabilizing the anterior cervical column [ 10 , 11 , 17 , 18 ]. For instance, Waschke et al treated nine patients with a standard one-level or two-level cervical corpectomy using an expandable titanium cage followed by anterior plating and vertebroplasty [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The technique, including ventral cervical plate and cement augmentation, is designed to restore structural integrity. This method aligns with findings from prior studies that have demonstrated positive outcomes, with similar procedures aimed at stabilizing the anterior cervical column [ 10 , 11 , 17 , 18 ]. For instance, Waschke et al treated nine patients with a standard one-level or two-level cervical corpectomy using an expandable titanium cage followed by anterior plating and vertebroplasty [ 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…Bayley et al’s treatment of seven patients with ventral vertebral augmentation introduced 0.2–0.25 mL of Kyphon cement into the screw holes prior to securing the anterior plate, also resulting in a complication-free seven-month follow-up period [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation